Diatomáceas bioindicadoras de qualidade da água no Lago do Juá – Santarém/PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The Amazon is internationally known for the biological, landscapes, forest, and river ecosystems’ diversity. Between its strategic cities, Santarém/Pará stays in between the confluence of Tapajós and Amazonas rivers and passed through physical structure changes and had its social and economic relations strongly associated with the river environment. With that, the management and monitoring of the water resources to avoid environmental damages, promote sustainability and to keep balance becomes necessary for the economic development of and water availability in quantity and quality. The diatoms are seaweed that flock in all aquatic environments and have been presenting notoriety as biological indicators for the high richness of species and capacity to fastly answer the water alterations. Because of that, this study’s goal is to indicate what diatoms species that resides in lake Juá’s sediment can be used for the quality’s evaluation of the water. The collections were made in five samples’ stations in January (flood), April (high waters), July (ebb) and October (low waters) of 2021.The benthic diatoms were obtained through a specific collector and fixated with formaldehyde at 4%. Concurrently, the abiotic variables were obtained (physically, chemically and nutrients) through Standard Methods for the Examination of Water and Wastewater. The samples were submitted to oxidation for the elimination of organic matter to the mounting of permanent blades. The taxon identifications were made through classical literature. To determine the relative abundance of the found taxon, were counted at least 400 valves, and expressed as relative abundances. The diversity was expressed as richness and diversity Shannon (H’) index. Based on the presence and abstention of taxon, the consistency index was calculated. The association degree was verified through the Canon Correspondence Analysis (CCA). The physical and chemical data were analyzed through exploratory descriptive statistics, variance analysis and Main Components Analysis. There were identified 177 taxon of 32 gender. The most representative gender was Eunotia Ehrenberg (28%), Pinnularia Ehrenberg (18%), Surirella Turpin (7%), Frustulia Rabenhorst (5%). The lowest value of richness recorded was 32 species on E2 JUL station, corresponding to the ebb and the biggest was of 75 species on E5 ABR station, corresponding to the high waters. The Shannon-Wiener index values varied between 2,26 to 3,34. The frequency occurrence of the species presented a percentage of rare species (37%), sporadic (31%), frequent (19%) and constant (13%). The aggressions that lake’s Juá has been suffering along its length are causing a drastic mischaracterization of the landscape, due to the processes of territorial expansion. The present study is a pioneer in the state of Pará by addressing ecological information from a group that are excellent environmental bioindicators and comes to present ecological information that signals the need for biomonitoring, which will be able to contribute to the proposition of measures for the preservation and recovery of environments that suffered or are subject to anthropic actions.
Keywords: Bacillariophyceae; Impactos antrópicos; Indicadores biológicos; Lagos de inundação; Recursos hídricos; CNPQ:: ENGENHARIAS